Matrix Rhythm Therapy Versus Interferential Therapy Combined with Lumbar Stabilization Exercises in Chronic Non-Specific Low Back Pain: A Randomized Comparative Trial (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Chronic non-specific low back pain is a persistent musculoskeletal condition associated with pain, disability, impaired movement confidence, and reduced participation in daily life. Lumbar stabilization exercises are widely used in rehabilitation; however, the added value of different adjunct modalities remains uncertain.Objective: To compare the effects of Matrix Rhythm Therapy and Interferential Therapy, each combined with lumbar stabilization exercises, on pain intensity, disability, and multidimensional pain perception in individuals with chronic non-specific low back pain.Methods: Thirty participants with chronic non-specific low back pain were allocated to Matrix Rhythm Therapy plus lumbar stabilization exercises (MRT + LSE; n=15) or Interferential Therapy plus lumbar stabilization exercises (IFT + LSE; n=15). Interventions were delivered three times weekly for six weeks. Outcomes included the Numeric Pain Rating Scale (NPRS), Oswestry Disability Index (ODI), and McGill Pain Questionnaire, assessed at baseline and after intervention.Results: Both groups improved after treatment. The MRT + LSE group showed larger mean reductions in NPRS (5.13 points), ODI (28.80 points), and McGill Pain Questionnaire scores (29.86 points) than the IFT + LSE group, which improved by 2.33, 18.00, and 17.27 points, respectively. Summary-based between-group analyses favored MRT + LSE for NPRS, ODI, and McGill outcomes.Conclusion: Both interventions were associated with reductions in pain and disability; however, Matrix Rhythm Therapy combined with lumbar stabilization exercises produced greater improvements across all reported outcomes. Larger trials with corrected demographic reporting, allocation concealment, assessor blinding, and long-term follow-up are needed to confirm these findings.